ESPRESSIONI CON ANGOLI ASSOCIATI

sin(π - α) + cos(π/2 + α) + cos(π - α) + sin(π/2 + α) = 0 | tg(π/2 + α)·tg(π + α) + tg(π/2 - α)·tgα = 0 |

tg(π/2 + α)·tg(π + α) + tg(π/2 - α)·tgα = 0 | sin(π/2 + α)·cos(π - α) - sin(π/2 + α)·cos(π + α) = 0 |

sin(-α)·sin(π - α) + cos(-α)·cos(π - α) + 1 = 0 | tg(-α)·ctg(π/2 + α) - ctg²(π/2 - α) - tg(π - α) - tgα = 0 |

cos(π/2 + α)·cos(π - α) + sin(π/2 + α)·sin(π + α) = 0 | cos(5π/2 + α)·cos(5π/2 - α) - sin(π + α)·sin(π - α) = 0 |

sin(5π/4) + √2·cos(π/4) + √2·tg(π/4) + ctg(3π/4) = √2/2 | √2cos(π/4) + 2√3·sin(2π/3) - √3·tg(π/3) + 3·ctg(2π/3) = 1 - √3 |

√3·tg(7π/6) + sin(π/4)·cosec(π/4)
- 0.5·sec(π/3) + tg(7π/4) = 0 |
(2/√3)·tg(π/3) - (3/4)·ctg(π/4) +
sec(π) - 0.5·sin(5π/6) + sin(11π/6) = -1/2 |

√2·sin(π/4) - √3·cos(5π/6) +
tg(2π/3) - tg(-π/3) - cos(4π/3) = 3 |
√2·cos(-π/4) + 2√3·sin(2π/3) - √3·tg(π/3) - 3·tg(7π/6) = 1 - √3 |

2·sin(π/6) + 3·cos(π/3) + tg(4π/3) +
3·tg(2π/3) + 6·tg(7π/6) = 5/2 |
sin(π/6) + cos(π/6) + tg(π/6) + ctg(π/6) + sec(π/6) + cosec(π/6) = 5(√3+1)/2 |